Pengaruh Kenaikan Pajak Pertambahan Nilai (PPN) dan Harga terhadap Minat Beli Pelanggan Handphone Aland Cell di Kecamatan Muara Bulian Kabupaten Batang Hari - Sri Rosmawati; Budi Darma; Kasiyati Yunita Wulansari (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to analyze the effect of Value Added Tax (VAT) and price on consumer purchasing interest in mobile phones at the Aland Cell Store in Muara Bulian District, Batanghari Regency. This study uses a quantitative approach with a survey method. Data were collected through distributing questionnaires to consumers and analyzed using multiple linear regression. Hypothesis testing was carried out using a t-test to determine the partial effect, an F-test to determine the simultaneous effect, and a coefficient of determination (R²) test to measure the model's ability to explain the dependent variable. The results showed that consumer purchasing interest in mobile phones at the Aland Cell Store was not influenced by Value Added Tax and price, but rather by other factors.